2023
DOI: 10.1590/1518-8345.6820.4046
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas de Burnout entre médicos y enfermeros antes, durante y después de atender pacientes con COVID-19

Giselle Dayana Valdes-Elizondo,
Pablo Álvarez-Maldonado,
Maria Angélica Ocampo-Ocampo
et al.

Abstract: Objetivo: este estudio evaluó síntomas de Burnout entre médicos y enfermeros antes, durante y después de la atención provista a pacientes con la enfermedad COVID-19. Método: estudio comparativo y transversal realizado en la unidad de Atención Respiratoria de un hospital público de nivel terciario. Se empleó el Inventario de Burnout Maslach. Resultados: se distribuyeron 280 encuestas entre los tres períodos: antes (n=80), durante (n=105) y después (n=95) de la atención a pacientes con COVID-19; se obtuvieron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Our research showed that female healthcare workers appeared to be at higher risk of job burnout than male healthcare workers, suggesting possible gender differences in work experiences or ways of coping with stress. Similar to our study, other researchers also found that the female gender was more susceptible to burnout, especially during the COVID-19 pandemic [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research showed that female healthcare workers appeared to be at higher risk of job burnout than male healthcare workers, suggesting possible gender differences in work experiences or ways of coping with stress. Similar to our study, other researchers also found that the female gender was more susceptible to burnout, especially during the COVID-19 pandemic [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…It should also be emphasised that in our study, the risk of burnout was higher among nurses than among doctors and paramedics, which is also shown by other studies [ 27 , 35 ]. All this (gender, profession, and working time) should be taken into account in interventions to prevent burnout.…”
Section: Discussionsupporting
confidence: 88%